NARRATIVE POLICY FRAMEWORK: POLICY ON THE EXPANSION OF NEW AUTONOMOUS REGIONS (DOB) IN PAPUA - Ahmad Ahmad; Syarifah Syarifah; Fayra Nabillah Azza (Journal of Social Politics and Governance (JSPG), 2025)
This study aims to analyze how Indonesian policymakers make decisions regarding the expansion of DOBs in Papua, with a focus on public narratives in the media. To see the public narrative, a Narrative Policy Framework (NPF) study will be conducted which can describe, explain the structure of public narratives in policy making. The research method uses a qualitative approach with the support of QDAS (Qualitative Data Analysis Software), and the research data sources come from trusted online media in Indonesia. The results showed that the conversation about DOB expansion in Papua was dominated by the central and local governments. This indicates that the DOB expansion policy in Papua is dominated by political elites, so it has the potential to cause conflict because it is not in accordance with the aspirations of the community. The expansion process also has the potential to trigger conflicts between the expanded regions, especially if the distribution of resources and power is not fair and transparent. The implication is that active community participation in decision-making on regional expansion is important so that policies reflect the aspirations and real needs of the Papuan people and reduce the dominance of political elites.